Para uma análise critica da orientação educacional: subsídios para compreensão e definição de sua pratica no Brasil - Teixeira, Rita Amelia (1979)
The main purpose of this study is to identify the prevailing conditions of school guidance in Braz.il that can be blamed for the difficulties that such activity has been up against in its ittempt to become respected and made effective in Brazil's schools. This descriptive study is organized in five chapters in which pertinent information emerging basically from references found in the available literature (books . journals, documents. research work) is anaIyzed. Clapter 1 briefly presents the theoretical ground work upon which school guidance is an activity has been founded. Chapter 2 introduces a summary of school guidance the way it is carried out in the United States, since we’re focused on the way school guidance takes place in the American School System as a reference point for the interpretation of its applicability in Brazilian schools. Chapter 3 deficts school guidance praxis in the Brazilian School System, pointing out facts that highlight the obvious gap between the objectives and the principles set forth by school guidance in Brazil, its perspectives of becoming effective and the frame of inconsistencies for which it is know and criticized. Chapter 4 presents an analysis and an interpretation of the causes that are believe to be responsible for the difficulties school guidance faces in getting a stronghold in Brazil's schools. These uncertainties and concerns have been centered around three basic hypothesis that might explain the indefinition of its practice and the dissatisfaction of the professionals in change of makind it effective. Chapter 5 presents suggestions and proposals of further studies that might be pursued in order to help define school guidance in the Brazilian School System and make it a really useful practice in the educational process.